The contribution of the reading habit, vocabulary mastery, and grammar to the experience writing skill of 5th grade students of state elementary schools - Noraning Diarani; Kastam Syamsi (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2019)
This study aims to find out the contribution of reading habit, vocabulary mastery, and grammar mastery to the experience writing skill of the 5th grade students of state elementary schools in Bambanglipuro Subdistrict, Bantul, Yogyakarta. This study is an ex-post facto using the correlational quantitative research approach. The population comprised all 5th grade students of state elementary schools in Bambanglipuro Subdistrict, Bantul, Yogyakarta totaling 300 students. A sample of 169 students was established using the proportional random sampling technique. The instruments consisted of a test and questionnaire. The test was used to measure the vocabulary mastery, grammar mastery, and experience writing skill. The questionnaire was used to measure reading habit. The data were analyzed using the multiple regression analysis. The results show that there is a significant and positive contribution among reading habit, vocabulary mastery, and grammar mastery to the experience writing skill.